Breaking the karmic complex: the role of transpersonal phenomena in psychotherapy with an adult survivor of child abuse : a clinical case study - Oberholzer, Sofia Adriana (Rhodes University, Faculty of Humanities, Department of Psychology, 1997)
This longitudinal study addresses the interface between the emerging paradigm of Transpersonal Psychology, which recognizes the transbiographical domain of consciousness, and the clinical area of child abuse. By using the transpersonal concept of the karmic complex, which was developed in the discourse of Roger Woolger, it explores the clinical value of past-life regressions and other transpersonal phenomena in the therapeutic process. The study provides an in-depth phenomenological description and a theoreticalheuristic explication of the experience of a single subject who was an adult survivor of physical and sexual abuse as well as early emotional deprivation in childhood, and who, over a four-year period of intensive psychotherapy, experienced a wide spectrum of transpersonal phenomena which included 123 past-life regressions. The therapeutic process could be clearly delineated into a biographical phase, which was dominated by biographical traumas, and a subsequ~nt transpersonal phase, during which the focus was almost exclusively on transpersonal material. This provided the opportunity to explore the therapeutic impact of trans personal mechanisms" of healing on an interlocking constellation of complexes in terms of achieving an integration of archetypal opposites in the psyche. The study provides strong support for transpersonal concepts about the nature of consciousness, as developed by Grof and Woolger. It affirms spirituality as an intrinsic property of the psyche, and verifies that the healing of psychological trauma is on a continuum with the process of spiritual purification and growth. The ,study establishes support for the clinical value of the karmic complex as a conceptual tool and provides a systematic, extended analysis of the multi levelled processes involved in the breaking of the complex.
Keywords: Transpersonal psychology; Reincarnation; Adult child abuse victims -- Treatment